Numerical Simulation on Jet Forming and Penetration Performance of Several Amorphous Energetic Alloy Liner with Typical Structures. Issue 1 (June 2021) - Cui, Ping; Shi, Dongmei; Xu, Jingqing; Wang, Tianci; Zhang, Xingze; Li, Zhuang; Wang, Deshi
Abstract: The structure and material of the liner are the key factors that affect the forming and penetration ability of the jet. In order to study the influence of new energetic materials and typical liner shapes on jet forming and penetration behavior, this paper takes ZrCuNiAlAg amorphous alloy as the liner material and establishes four shaped charge (SC) models with conical, sub-hemispherical, eccentric sub-hemispherical and hypercumulative liners respectively. The jet forming law and its penetration process against the concrete target plates under different liner shapes are studied based on the AUTODYN numerical simulation software. The results show that a stable jet can be formed from ZrCuNiAlAg amorphous alloy liner under the Mohaupt effect, but the jets produced by liners with different structures differs quite a lot. Under the same conditions including charge diameter, charge length diameter ratio and wall thickness, the tip velocity, the tip-tail velocity difference and the length of the jet formed by conical and hypercumulative liners are significantly higher than those of sub-hemispherical and eccentric sub-hemispherical liners. The jet length of the hypercumulative liner is the longest while that of the eccentric sub-hemispherical liner is the shortest. The hypercumulative jet can penetrate a concrete target plate with 400mm thickness at 250μs, and the jets formed by conical, sub-hemispherical and eccentric sub-hemispherical liners basically stops the penetration ability at 300μs. In terms of penetration depth, the hypercumulative liner is the largest and the sub-hemispherical liner is the smallest. The sub-hemispherical liner gets the largest perforation aperture. The eccentric sub-hemispherical liner gets the best comprehensive effect of penetration and expansion against the concrete target. The results of this paper can be used for reference in the structural design of the amorphous alloy liner.